Etika penggunaan AI dalam Pelayanan publik Dari perspektif Administrasi Negara - Aqsha Fatiha Juwita; Faizah Mutmainnah; Farhan Ergi Aldino; Khusnulita Fatma Rhamadhani; Yulia Hanoselina; Yuliarti Y (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Advances in digital technology have led to the increasing adoption of Artificial Intelligence (AI) across various areas of government, with the aim of making public services more effective and time-efficient. The use of AI technology in public services can provide many benefits, such as speeding up service processes, improving decision-making accuracy, and making it easier for the public to access these services. However, the use of AI also presents various ethical issues, such as the tendency for bias in algorithms, a lack of transparency in the system, the protection of personal information, and accountability for decisions generated by the technology. This study aims to examine the ethical considerations of using AI in public services from the perspective of Public Administration, as well as to identify the challenges and steps needed to establish an AI management framework that aligns with ethical principles. The study is grounded in the theory of Good Governance, which integrates the principles of public ethics and public accountability into a single, coherent theoretical foundation for its analysis. The method used is a qualitative approach in the form of a literature review. Data collection was conducted by gathering information from various documents, such as books, journals, legal regulations, government reports, and policy documents related to artificial intelligence and public services. The data were analyzed descriptively through the stages of reduction, presentation, and drawing conclusions. Research shows that AI has great potential to improve the quality of public services by automating services, processing data more quickly, and making the government more responsive to the needs of the public.